2021
DOI: 10.1109/access.2021.3065214
|View full text |Cite
|
Sign up to set email alerts
|

Compressive-Sensing-Aided MIMO Radar Enabling Multi-Functional and Compact Sensors in Air Scenarios Using Optimized Antenna Arrays

Abstract: We address the problem of direction-of-arrival (DoA) estimation for air targets using a compact, multi-functional radar sensor. In order to enhance the angular resolution of such sensors while exploiting the sparseness of typical air scenarios, we consider the combination of a multipleinput multiple-output (MIMO) radar approach with suitable compressive-sensing (CS) techniques. In particular, we investigate the combination of MIMO processing for two-dimensional (2D) antenna arrays with CS-based angular process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Local trust zones [225]- [230] Mapping [231] Massive twinning [232] Indoor [231] Outdoor [228]- [230] mmWave/THz [226], [228], [229] Sensors [225], [227], [229]- [231] Beamforming [226] Radar [228] , VLP [232] RSS, TDoA, DoA, RMSE…”
Section: Compressive Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Local trust zones [225]- [230] Mapping [231] Massive twinning [232] Indoor [231] Outdoor [228]- [230] mmWave/THz [226], [228], [229] Sensors [225], [227], [229]- [231] Beamforming [226] Radar [228] , VLP [232] RSS, TDoA, DoA, RMSE…”
Section: Compressive Sensingmentioning
confidence: 99%
“…Furthermore, Salari et al, in [227], documented a CSbased approach for obtaining TDOA estimates, which requires a limited number of signal samples, leading to a significantly lower computational complexity. A CS-aided MIMO scheme for aerial scenarios was reported in [228]. In more detail, the authors combined MIMO techniques for 2D antenna arrays and CS-based DoA estimation for 3D target tracking.…”
Section: A Conventionalmentioning
confidence: 99%
“…Local trust zones [257]- [262] Mapping [263] Massive twinning [264] Indoor [263] Outdoor [260]- [262] mmWave/THz [258], [260], [261] Sensors [257], [259], [261]- [263] Radar [260], VLP [264] Beamforming [258] RSS, TDoA, DoA, RMSE Multidimensional Scaling Robots [265] Local trust zones [266]- [274] Massive twinning [275] Indoor [265], [272], [275] Outdoor [267]- [269], [271], [274] Non-terrestrial [270], [273] Sensors [265]- [275] ToF, TDoA, RSS, RMSE…”
Section: Compressive Sensingmentioning
confidence: 99%
“…Furthermore, Salari et al, in [259], documented a CS-based approach for obtaining TDOA estimates, which requires a limited number of signal samples, leading to a significantly lower computational complexity. A CS-aided MIMO scheme for aerial scenarios was reported in [260]. In more detail, the authors combined MIMO techniques for 2D antenna arrays and CS-based DoA estimation for 3D target tracking.…”
Section: ) Compressive Sensingmentioning
confidence: 99%
“…A promising way to use fewer samples while achieving high accuracy is provided by the concept of compressive sensing (CS), which is a class of techniques able to solve underdetermined systems of linear equations with sparse inputs [26][27][28]. CS has been applied to many different domains in radar signal processing [29], for example, to reconstruct sparse signals with sampling rates far below the Nyquist-rate [30,31], for DoA estimation [32,33], array design [34], and extended target detection [35]. In terms of hardware design, it has been shown that CS performs well with pseudo-random array topologies [34,36] and also with widely separated antenna arrays with inter-element spacing d > λ [37,38].…”
Section: Introductionmentioning
confidence: 99%